Outside employment opportunities, employee productivity, and debt discipline - Kale, Jayant R.; Ryan, Harley E.; Wang, Lingling (Journal of Corporate Finance, 2019)
Using a sample of over 99,000 firm year observations encompassing extgreater13,800 firms from 1978 to 2007, we analyze how changes in labor market conditions influence the disciplining effect of debt on employee productivity. We document that better (worse) outside employment opportunities weaken (strengthen) the disciplinary effect of debt on employee output. The influence of outside employment options on leverage-output relation is robust to various controls for endogeneity, including using instrumental variables, a quasi-natural experiment, both firm and industry-level analysis, alternative model specifications, and controls for employees' work conditions and changes in work efficiencies. Altogether, our findings highlight the importance of labor market conditions on the efficacy of corporate financial policies and our understanding of how these policies influence economic outcomes.